Study of rain attenuation consequence in free space optic transmission - Rahman, A. K.; Anuar, Mat Safar; Syed Alwee Aljunid, Syed Junid; Junita, Mohd Nordin (Institute of Electrical and Electronics Engineering (IEEE), 2009)
Link to publisher's homepage at http://ieeexplore.ieee.org